The The Impact of Pandemic Writing on EFL Students' Critical Thinking Skills: An Exploratory Study: English - Anselmus Sudirman; Adria Vitalya Gemilang; Thadius Marhendra Adi Kristanto; Hendrikus Male; Rahman Kurniawan (Prodi Tadris Bahasa Inggris, 2023)
Pandemic writing contributes significantly to online writing activities in which EFL students build a solid foundation of critical thinking skills, not to mention their massive impact. This study aims to describe (1) aspects of pandemic writing that influence students' critical thinking skills during the COVID-19 period and (2) the contributions of pandemic writing to EFL students’ writing skills. This exploratory research involved thirty participants who were interviewed in-depth to obtain more meaningful information and insights using a purposive sample technique. During the analytical steps of sorting and comparing data, principles, and types and considering their relationships by composing notes from interview transcriptions, the data were reorganized and analyzed to elicit codes, data, categories, or narratives. Results show that the impact of pandemic writing on EFL students' critical thinking skills is mainly based on learning autonomy (30%), critical inquiries (6.7%), synchronous platforms (10%), rhetorical functions (16.7%), critical mindsets (13.3%) and cognitive framework (23.3%). Pandemic writing and its componential parts determine the development of EFL students' critical thinking skills, which range from the impact of brainstorming ideas to refined steps of revising paragraphs and the essay as a whole. Keywords— pandemic writing; critical thinking skills; cognitive framework; rhetorical functions; critical mindsets; problem-solving